(3eYGQL GdacQ GdhgjL aj Md eTcdGJ GdRjLs - (3eMeO Hf CHj HcQ Hf eMeO Hf MSf Hf Ydj GdaGQSj , HOQ GdOjf CHh YHO Gddg,J (B677 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg GdWhjdg (B: (3aQCjJ Cf CDda cJGHkG cGajkG hCHfi ajg HjGfkG TGajkG jQSe GdNRGFf GdSdWGfjg dCfGd GdNW GdChaQ hGdTQa GdCcHQ s
(3BNQgG (B:s
(3hcGf HGdShGO agh decg dJHfi ddfGXQ HGdYjGf hGddg Gdehab s
(3GdSdWGf GdPi Cdag dg GdcJGH gh TeS GdOjf jhSa Hf Gdedc efUhQs
(3ajgG cKjQ ef GdQShe GdgfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B117s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B98 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs